If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65x + 45 = 50x + 30 Reorder the terms: 45 + 65x = 50x + 30 Reorder the terms: 45 + 65x = 30 + 50x Solving 45 + 65x = 30 + 50x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-50x' to each side of the equation. 45 + 65x + -50x = 30 + 50x + -50x Combine like terms: 65x + -50x = 15x 45 + 15x = 30 + 50x + -50x Combine like terms: 50x + -50x = 0 45 + 15x = 30 + 0 45 + 15x = 30 Add '-45' to each side of the equation. 45 + -45 + 15x = 30 + -45 Combine like terms: 45 + -45 = 0 0 + 15x = 30 + -45 15x = 30 + -45 Combine like terms: 30 + -45 = -15 15x = -15 Divide each side by '15'. x = -1 Simplifying x = -1
| -2+4(5x+2)= | | 32x-.21x=195+12x | | cos(x)+cos(2x)=-1 | | y^2+12y+36=r | | g(-3)=2x^3+2 | | -2x+10=3x+45 | | -2*25+2y=44 | | c/4=1`6 | | 0.03(y-7)+0.14y=0.07y-0.20 | | 9x(2x-4)= | | 3x-9y=-21 | | 13=1-13 | | 27x+14=3(9x-7) | | 2e-8=14# | | -5(6x-4)= | | 6f=-5x+2 | | Y-5x=-8 | | 2x^2+5=-32 | | (-35)x(-14)x(0.5)= | | -81-4(7-3x)=13(x-8) | | 84-48/8 | | .25t+9=3 | | 2x-10x=30 | | (4x-9)(10x+5)=0 | | f(x)=-5x^2+2x-1 | | x^2-4x/x | | 2*-10-9y=38 | | 46-1+8x=18x-15 | | 6n-3-9n=4+2n-8 | | 28-3c+4=2c+6+1c | | 18/5-2k=6 | | 11x-7=7+9a |